Sensitivity analysis of RC frame failure time in fire conditions after removal column under progressive collapse - Majid Moradi (Iranian Society of Structrual Engineering (ISSE), 2021)
Consecutive loads can be a serious threat to the safety of structures. Abrupt removal of elemental elements such as columns is one of the causes of progressive failure in structures. The local breakdown caused by the sudden removal of the column can affect the behavior of the structures of successive courts. One of the loads that threatens the safety of the structure over the life of the structure is the fire.When a structure can withstand the load, one of the main factors in the safety of structures against thermal loads. Local loopholes in the structure, including the sudden removal of barrier elements, can affect the stability of structures against fire load as two successive events. In this research, the susceptibility of the RC frame to the stability of the continuous loading of the column and the subsequent fire is compared to the random variables.The 7-story concrete frame is modeled after mechanical design and is subject to the sudden removal of the column in different situations. Several parameters have been considered as random variables, and two methods of Monte Carlo and second-order second-order sensitivity analysis (FOSM) have been used for sensitivity analysis.  Sensitivity analysis in a concrete frame for the analysis of dynamic duct and thermal analysis has been done separately. The results show that in the sudden removal of the column, the dead load, and in the subsequent fire scenario, the dead load and reinforcement coatings have the most sensitivity to other parameters. Also, the maximum sensitivity error of the FOSM method was calculated to be 11% compared to the Monte Carlo method.